Tingkat Culture Shock pada Mahasiswa Keperawatan Program Profesi Ners - Ayu, Rahadiani; Pahria, Tuti; Sriati, Aat; Rahayu, Kusila Devi (Journal of Telenursing (JOTING), 2024)
This research aims to determine the level of culture shock in nursing students in the professional nurse program at STIKes Dharma Husada Bandung. The research method used is a quantitative descriptive method. The research showed that 60 nursing students in the STIKes Dharma Husada Bandung professional nurse program experienced moderate culture shock (100%). In conclusion, the level of culture shock experienced by nursing students in the professional nurse program at STIKes Dharma Husada Bandung is in the medium category. Keywords: Culture Shock, Nursing Students, Professional Nurse Program